Phytoremediation of iron-contaminated soils using humic acid and hyperaccumulator grasses - Cahyo, Zumatul Atiko Islamya; Wanti Mindari; Aditya, Haidar Fari (Universitas Lancang Kuning, 2024)
The Lapindo mud disaster in Porong, Sidoarjo, Indonesia, resulted from mining activities, leading to severe iron (Fe) contamination in the soil. This contamination has adversely impacted agricultural productivity in the affected areas. Phytoremediation, utilizing humic acid as a chelating agent and hyperaccumulator grasses, is a potential solution to mitigate this pollution. This study employed a factorial completely randomized design (CRD) to evaluate this approach with two factors: the application of 600 ppm humic acid and the use of different grasses (vetiver, elephant grass, nutgrass, and gotu kola). Observed parameters included plant dry weight and total iron content in soil and plant tissues. These data were used to determine the bioconcentration factor (BCF), translocation factor (TF), and absorption efficiency (%). The results indicated that humic acid significantly increased plant dry weight and iron uptake in plant tissues. The combination of gotu kola and humic acid showed the highest phytoremediation potential, with a BCF of 0.3121, TF of 1.4871, and an absorption efficiency of 55.7538%. This study highlights the effectiveness of humic acid and hyperaccumulator grasses in phytoremediation of iron-contaminated soils, offering a sustainable approach to improving soil health and agricultural productivity in polluted areas.